Gloss to the decision of the Supreme Court of October 5, 2023, I NSW 70/23 - Kołbuc, Michał (Studia Iuridica Toruniensia, 2026)
The commented judgment is the result of proceedings before the Supreme Court initiated as a result of a complaint against the resolution of the National Electoral Commission No. 211/2023 regarding guidelines for district electoral commissions regarding the tasks and mode of preparation and conduct of voting in voting districts established in the country in elections to the Sejm and Senate of the Republic of Poland and in the national referendum ordered for October 15, 2023. The author analyzes the ruling, its motives, and argumentation appointed by the Supreme Court. The legal issues raised focus on the legal admissibility of appointing a social observer of the referendum by appropriately applying the provisions of the Electoral Code to the referendum procedure. In the commentary, the author also deals with the issue of the Supreme Court’s ability to review the resolution ordering the referendum, including review of referendum questions in the context of the constitutionally defined competences of the Sejm of the Republic of Poland and the President of the Republic of Poland. In his work, the author used the formal-dogmatic method and reviewed and analyzed both the achievements of the electoral law doctrine and court jurisprudence.